Strategy Based Technology-Based Startups to Drive Digital Business Growth - Hanny Safitri; Mochamad Heru Riza Chakim; Alfri Adiwijaya (Startupreneur Business Digital (SABDA Journal), 2023)
Lean startup methodology-based strategic formulation to promote the expansion of  technology-based startup businesses in Indonesia. About 75% of developing startups fail to expand appropriately, which is a relatively high startup failure percentage. Failure of startups is influenced by time and the relevant industry. Due to the wrong approach being chosen from the startup's first year to its fourth, it was unable to expand. The goal of this study is to develop new general methods for company growth based on the lean startup approach. The goal of this study is to use the Delphi technique to find startup failure indicators, and then to select the primary failed cause using the Analytical Network Process (ANP). The research's next phase is to develop the plan after the failure factor has been determined. The researcher acquired 8 as a consequence of this study. 55 indicators of startup failure factors and factors. Using the ANP model, 10 priorities were determined. addressed by developing a new approach utilizing agile development and the minimal viable product idea. technique, human resource management, and customer relationship management. eventually acquired a fresh approach that entrepreneurs may utilize to promote growth.